2021
DOI: 10.3390/pr9101742
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Network Pharmacology of Moringa oleifera Combined with Gemcitabine against Pancreatic Cancer

Abstract: Gemcitabine (GEM) is the first-line chemotherapy drug for patients with advanced pancreatic cancer. Moringa oleifera (MO) exhibited various biological activities, including anticancer effects. Nevertheless, the effectiveness of their combination against pancreatic cancer has not yet been explored. This study evaluates the effect of MO and GEM against pancreatic cancer through network pharmacology. TCMSP, TCMID, and PubMed were used to identify and screen MO bioactive compounds. MO and GEM genes were predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(88 reference statements)
1
0
0
Order By: Relevance
“…This result of current study refers to the presence of an enhancement in the anti-proliferative effect of docetaxel when combined with an ethanolic extract of Moring oleifera (seeds and leaves). This finding is consistent with a recent study by (Sahruddin et al, 2021), which found that combining gemcitabine with M oleifera extract improved the chemotherapeutic effect of gemcitabine on pancreatic cancer. The current study's findings are also consistent with the findings of , who found that an ethanolic extract of Moringa oleifera synergized the antiproliferative effect of vesicular stomatitis virus, which has been used as oncolytic viral therapy against cervical cancer cells.…”
Section: Effect Of the Combination Of Ethanolic Extract Of Moringa Ol...supporting
confidence: 93%
“…This result of current study refers to the presence of an enhancement in the anti-proliferative effect of docetaxel when combined with an ethanolic extract of Moring oleifera (seeds and leaves). This finding is consistent with a recent study by (Sahruddin et al, 2021), which found that combining gemcitabine with M oleifera extract improved the chemotherapeutic effect of gemcitabine on pancreatic cancer. The current study's findings are also consistent with the findings of , who found that an ethanolic extract of Moringa oleifera synergized the antiproliferative effect of vesicular stomatitis virus, which has been used as oncolytic viral therapy against cervical cancer cells.…”
Section: Effect Of the Combination Of Ethanolic Extract Of Moringa Ol...supporting
confidence: 93%